(untitled) (Journal of Comparative & International Higher Education, 2022)
Developing and implementing impactful international partnerships was the top priority for higher education institutions prior to the pandemic breakout. The pandemic forced higher education to change and act quickly to avoid international enrollment crash and spurred some unprecedented international collaborations. This case study examines an unconventional international cooperation that a public research university in China initiated for providing a college learning environment for Chinese students enrolled in other countries during the global challenge. This study responds to the call for how to build sustainable internationalization. The research findings contribute to the development of a new paradigm of internationalization and creative internationalization for the future of new normal.